Richard III - Shakespeare, William, 1564-1616 (Shakespeare, William, 1564-1616. Works. 2003., 2008)
Treacherous, power-hungry, untempered by moral restraint, and embittered by physical deformity, Richard, the younger brother of King Edward IV, is ablaze with ambition to take England's throne. Richard III, Shakespeare's long chronicle of Richard's machin.